El Conocimiento En La Pyme, Factor Clave Para La Innovación Y La Rentabilidad - Luis Enrique Valdez Juárez; Elba Alicia Ramos Escobar; Gonzalo Maldonado Guzmán (European Scientific Journal, ESJ, 2017)
The purpose of this article is to examine the effects of internal and external knowledge on innovation and also how innovation influences the profitability of Small and Medium Enterprises (SMEs). The research is focused on a sample of 412 companies from the industrial and services sectors of the southern region of the State of Sonora, Mexico. Data collection was carried out from June to October 2014, with the support of a selfdirected survey of company managers. For the analysis of the model and validation of the structured relationships, the structural equation method (SEM) based on the variance has been used through the use of the PLS technique (Partial Least Square) with support of the software SmartPLS version 3.2.6 Professional. The results show that both internal and external knowledge have a positive and significant influence on the innovation in products and processes that is developed in SMEs. In addition, product innovation has a significant and positive impact on the profitability of companies. In contrast, a significant but negative relationship was found between process innovation and the profitability of SMEs. It is important that owners and managers continue to capture and use knowledge in order to improve innovation. In addition, it is advisable to implement plans and actions to improve product and process innovation to raise the level of profitability. This work contributes mainly to the development of the literature on absorption capacity (CA) and the theory of resources and capabilities (R&C).